Upskilling B40 Food Microentrepreneurs through Digital Non-Formal Lifelong Learning (E-NLL): A Preliminary Study - Xue Fa TONG; David Yoon Kin TONG; Han-Foon NEO; Chee Hian CHUA; Ilham Akbar ALFATIHAH (Communications of International Proceedings, 2022)
Street food microenterprises play an important role in reinvigorating tourism destinations and in expressing the comforting flavours of the local culinary food heritage. But the impact of the COVID-19 pandemic on the food and beverages (F&B) sector has challenged the existing resilience of these microenterprises. B40-microentrepreneurs forms the largest self-employed group whose knowledge, skills and abilities (KSAs) in costing and business innovation will need upgrading. Existing socioeconomic barriers has hindered the receptiveness of these entrepreneurs in acquiring the necessary KSAs to improve on their current business models. This research purposes the Kolb’s Experiential Learning Theory (ELT) to design a non-formal lifelong learning (NLL) module to better fit to the learning needs of these B40-entrepreneurs. The NLL programme carries a more hands-on and interactive andragogy to educate and upskill the KSAs. The proposed learning module is developed on a three-staged project: fieldwork, prototype development and upskilling workshop. This article presents the second stage of the research on developing prototype applications that are targeted for the B40-entrepreneurs’ use. The developed applications are intended as part of a reinforcing learning session for the third stage of the project. Preliminary findings from a User Acceptance Testing (UAT) indicates a general acceptance of the mobile learning applications, especially on the dual-language function. The paper offers an insight on the potential of a self-paced e-NLL prototype as a step forward to face-to-face driver model of blended learning to support the microentrepreneurs (users) in informally learning the related concepts on innovation and costing using actual business experiences.
Keywords: lifelong learning; microentrepreneurs; non-formal learning; mobile learning applications